INDIKASI KEDARURATAN MEDIS DALAM TINDAK PIDANA ABORSI OLEH TENAGA MEDIS: ANALISIS PUTUSAN NOMOR 36/PID.SUS/2024/PN DPS - Salman Naufal Haq; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
The involvement of medical personnel in unlawful abortion practices raises complex legal issues because it contradicts their professional obligation to provide healthcare services in accordance with ethical standards, professional competence, and applicable legal regulations. Although Law Number 17 of 2023 concerning Health permits abortion under limited circumstances, its implementation is strictly regulated through medical emergency indications, professional competence requirements, and healthcare service procedures as stipulated in Government Regulation Number 28 of 2024. This study aims to analyze the fulfillment of the legal requirements for medical emergency indications and to examine the judicial reasoning underlying the non-imposition of additional criminal sanctions in Decision Number 36/Pid.Sus/2024/PN Dps. This research employs a normative legal method with a descriptive-analytical approach using statutory, case, and conceptual approaches. Primary legal materials, consisting of the Indonesian Criminal Code, Law Number 17 of 2023 concerning Health, Government Regulation Number 28 of 2024, and Decision Number 36/Pid.Sus/2024/PN Dps, were analyzed qualitatively through legal interpretation and doctrinal analysis of the court's legal reasoning. The findings demonstrate that the abortion performed by the defendant did not satisfy the legal criteria for a medical emergency because there was no condition threatening the life or health of the pregnant woman or the fetus, the procedure was not carried out by a physician possessing the legally required professional competence and authority, and the mandatory healthcare procedures prescribed by the applicable legislation were not fulfilled. The study further reveals that the court did not impose the additional penalty of revoking the defendant's professional rights because the defendant did not possess a valid Certificate of Registration (Surat Tanda Registrasi—STR), Practice License (Surat Izin Praktik—SIP), or any legally recognized professional authority that could be revoked under Indonesian criminal law. The novelty of this study lies in its comprehensive analysis of the relationship between medical emergency indications, the professional authority of medical personnel, and the application of additional criminal sanctions within the framework of Indonesia's post-reform health law under Law Number 17 of 2023. This study concludes that consistent legal interpretation of medical emergency indications, coupled with strengthened supervision of professional competence among medical personnel, is essential to ensuring legal certainty, protecting patients' rights, and enhancing accountability within the healthcare profession.Keywords: Medical Emergency Indications; Abortion; Medical Personnel; Criminal Liability; Court Decision